Use of lean tools for continuous improvement in a practical cas in a manufacturing industry - Márquez Figueroa, Luis; Rodríguez, Netzemany; Pérez Domínguez, Luis; Romero, Roberto; Lopez, Francisco (2021)
Training is a wide field within the industries, this research covers the job instruction part, the technical training, based on the TWI–JI (Training Within Industry–Job Instruction) and the 4 steps training method. Simulation, based on Promodel®, propose reduce the effort to know the results in the long-term for the proposal improvements. Training within industries provide a solid foundation for the standards methods. Simulating a production line helps to see the impact of the proposed applications in the productive area and with these data decide if the pilot area could be replicated in other similar ones.